RiseTx: testing the feasibility of a web application for reducing sedentary behavior among prostate cancer survivors receiving androgen deprivation therapy - Linda Trinh; Kelly P. Arbour-Nicitopoulos; Catherine M. Sabiston; Scott R. Berry; Andrew Loblaw; Shabbir M. H. Alibhai; Jennifer M. Jones; Guy E. Faulkner (BMC, 2018)
Abstract Background Given the high levels of sedentary time and treatment-related side effects in prostate cancer survivors (PCS), interventions targeting sedentary behavior (SED) may be more sustainable compared to physical activity (PA). Purpose To examine the feasibility of a web-based intervention (RiseTx) for reducing SED and increasing moderate-to-vigorous physical activity (MVPA) among PCS undergoing ADT. Secondary outcomes include changes in SED, MVPA, light intensity PA, and quality of life. Methods Forty-six PCS were recruited from two cancer centres in Toronto, Ontario, Canada between July 2015-October 2016. PCS were given an activity tracker (Jawbone), access to the RiseTx website program, and provided with a goal of increasing walking by 3000 daily steps above baseline levels over a 12-week period. A range of support tools were progressively released to reduce SED time (e.g., self-monitoring of steps) during the five-phase program. Objective measures of SED, MVPA, and daily steps were compared across the 12-week intervention using linear mixed models. Results Of the 46 PCS enrolled in the study, 42 completed the SED intervention, representing a 9% attrition rate. Measurement completion rates were 97 and 65% at immediately post-intervention and 12-week follow-up for all measures, respectively. Overall adherence was 64% for total number of logins (i.e., > 3 visits each week). Sample mean age was 73.2 ± 7.3 years, mean BMI was 28.0 ± 3.0 kg/m2, mean number of months since diagnosis was 93.6 ± 71.2, and 72% had ADT administered continuously. Significant reductions of 455.4 weekly minutes of SED time were observed at post-intervention (p = .005). Significant increases of + 44.1 for weekly minutes of MVPA was observed at immediately post-intervention (p = .010). There were significant increases in step counts of + 1535 steps from baseline to post-intervention (p < .001). Conclusions RiseTx was successful in reducing SED and increasing MVPA in PCS. PCS were satisfied with the intervention and its components. Additional strategies may be needed though for maintenance of behavior change. The next step for RiseTx is to replicate these findings in a larger, randomized controlled trial that will have the potential for reducing sedentary time among PCS. Trial registration NCT03321149 (ClinicalTrials.gov Identifier).